Microbiologically Influenced Corrosion of Copper and Its Alloys in Anaerobic Aqueous Environments: A Review - Amendola, Roberta; Acharjee, Amit (Frontiers in Microbiology, 2022)
Regardless of the long record of research works based on microbiologically influenced corrosion (MIC), its principle and mechanism, which lead to accelerated corrosion, is yet to be fully understood. MIC is observed on different metallic substrates and can be caused by a wide variety of microorganisms with sulfate-reducing bacteria (SRB) being considered the most prominent and economically destructive one. Copper and its alloys, despite being used as an antimicrobial agent, are recorded to be susceptible to microbial corrosion. This review offers a research overview on MIC of copper and its alloys in anaerobic aqueous environments. Proposed MIC mechanisms, recent work and developments as well as MIC inhibition techniques are presented focusing on potable water systems and marine environment. In the future research perspectives section, the importance and possible contribution of knowledge about intrinsic properties of substrate material are discussed with the intent to bridge the knowledge gap between microbiology and materials science related to MIC.